2020
DOI: 10.1111/vco.12622
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin‐induced myelosuppression as related to body weight in dogs

Abstract: Smaller dogs are known to have an increased risk of chemotherapy-induced myelosuppression for doxorubicin, mitoxantrone and melphalan. This retrospective study aimed to determine if dogs <15 kg and <10 kg experienced greater degrees of myelosuppression following treatment with carboplatin chemotherapy compared with dogs ≥15 kg. One hundred and one dogs treated with carboplatin for a variety of malignancies were retrospectively analysed. Eight dogs (61%) weighing <10 kg, three (38%) weighing 10 kg to <15 kg and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
(93 reference statements)
1
13
1
Order By: Relevance
“…No specific anticancer drug was revealed as a risk factor for severe neutropenia. Though, our study confirmed the higher risk to develop chemotherapy‐induced haematological sAE for small dogs (<10 kg), similarly to previous data 9,15,34–39 . Mortality rate among dogs with chemotherapeutic‐induced febrile neutropenia has been previously reported in 8.5% of cases 77 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No specific anticancer drug was revealed as a risk factor for severe neutropenia. Though, our study confirmed the higher risk to develop chemotherapy‐induced haematological sAE for small dogs (<10 kg), similarly to previous data 9,15,34–39 . Mortality rate among dogs with chemotherapeutic‐induced febrile neutropenia has been previously reported in 8.5% of cases 77 .…”
Section: Discussionsupporting
confidence: 91%
“…Risk factors for the development of AE were investigated in previous reports. In several studies, dogs with lower body weight had an increased risk of presenting AE 9,15,34–39 . In one retrospective study on 39 cases receiving chemotherapy, dogs with lymphoma were significantly more likely to develop febrile neutropenia than dogs with solid tumours 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Although Coffee et al (2020) found carboplatin-induced neutropenia and thrombocytopenia especially in dogs under 15.0 kg, the findings of the current study indicated no correlation between myelosuppression and body weight. However, it must be considered that the authors studied a canine population much larger than the current study (101 versus 21) which leads to higher statistical reliability.…”
Section: Discussioncontrasting
confidence: 95%
“…Anecdotally, many veterinarians have used lower carboplatin dose for smaller dogs than the MTD since these dogs are prone to severe myelosuppression 46 . Furthermore, a recent study reported that an increased risk of carboplatin‐induced myelosuppression in dogs <15 kg, and particularly those <10 kg 47 . Although systemic chemotherapy might be conceivable, particularly in dogs with risk factors for poor survival (≥T3, presence of metastatic disease, LVSI, dysgerminoma and adenocarcinoma), a future prospective study would be in a better position to evaluate the survival benefits of chemotherapy for these dogs.…”
Section: Discussionmentioning
confidence: 99%